Local Contents In The Arts Learning For Early-Age Students In Gunungpati - Tasuah, Neneng; Setiawan, Deni (Universitas Negeri Semarang, 2019)
The investigation is inspired by the cultural diversity of Indonesia, particularly the local contents in Semarang implemented through the world of early-childhood education. The study aims to identify the implementation of local contents in the arts learning in a play group in Gunung pati Semarang. This is theoretical study conducted in two phases as the strategies for field study implementation. The structured observation was conducted through documents, portfolio, questionnaires studies, and in-depth interviews. The data analysis was conducted thematically through date triangulation. The object was selected through purposive sampling of all populations totalled 47 play groups, then 14 were selected. The local contents were implemented in the arts learning in play groups in Gunungpati. The local contents comprise fine arts, dances, and music. Those contents were taken from the local cultures in Semarang in general and they reflect the local culture in Gunungpati.